RETRACTED: In Vitro Induction of Apoptosis in Isolated Acute Myeloid Leukemia Cells: The Role of Anastatica hierochuntica Methanolic Extract - Islam M. El-Garawani; Amira S. Abd El-Gaber; Noura A. Algamdi; Aamer Saeed; Chao Zhao; Omar M. Khattab; Mohamed F. AlAjmi; Zhiming Guo; Shaden A. M. Khalifa; Hesham R. El-Seedi (Metabolites)
Anastatica hierochuntica L. (Cruciferae) has been known in Egyptian folk medicine as a remedy for gastrointestinal disorders, diabetes and heart diseases. Despite the wide usage, A. hierochuntica research provides insufficient data to support its traditional practice. The cytotoxicity of A. hierochuntica methanolic extract was investigated on acute myeloid leukemia blasts (AML) and normal human peripheral leucocytes (NHPL). The phytochemical identification of bioactive compounds using 1H-NMR and LC-ESI-MS was also performed. A. hierochuntica extract caused non-significant cytotoxicity on NHPL, while the cytotoxicity on AML was significant (IC50: 0.38 ± 0.02 μg/mL). The negative expression of p53, upregulation of Caspase-3 and increase in the BAX/BCL-2 ratio were reported at the protein and mRNA levels. The results suggest that A. hierochuntica extract induced AML cell death via the p53-independent mitochondrial intrinsic pathway and further attention should be paid to this plant as a promising natural anticancer agent.